2019
DOI: 10.24925/turjaf.v7i1.87-91.2131
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Farm Mechanization in Nepal

Abstract: The paper attempts to explore the factors affecting the farm mechanization in Nepal, where agriculture is the primary livelihood of most people and the mechanization is crucial for efficient production and productivity. The government has also introduced a separate policy for agriculture mechanization in 2014. A primary data was collected from 300 households and analysed to assess and quantify the determinants of the farm mechanization. A descriptive analysis was carried out for understanding the data and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 3 publications
(4 reference statements)
2
11
0
Order By: Relevance
“…score of 59.5 and 31 and stationed at the 2 nd and 3 rd position, respectively. Similar problems had been reported by Loon et al, 2020, Balachandran, 2004Arun et al, 2019. Rich farmers were bene tted from the different government subsidy schemes.…”
Section: Constraints Analysis For Strategy Formulation For Out Scalinsupporting
confidence: 81%
See 1 more Smart Citation
“…score of 59.5 and 31 and stationed at the 2 nd and 3 rd position, respectively. Similar problems had been reported by Loon et al, 2020, Balachandran, 2004Arun et al, 2019. Rich farmers were bene tted from the different government subsidy schemes.…”
Section: Constraints Analysis For Strategy Formulation For Out Scalinsupporting
confidence: 81%
“…An effort was also made to quantify the additional economic bene t by using the Apparently Unrelated Regression (SUR) model to apply selected forms of machinery to different varieties. Seed cum fertiliser drill and zero tillage results have been found to increase yield by 13.39 quintals and 6.0 quintals per ha respectively and decrease the seed rate by 27.71 kg/ha and 24.20 kg /ha, respectively, for the HD 2967 wheat variety. The growth of the agricultural mechanisation sector is hindered by machine cost, the widespread existence of resource poor farmers, and inaccessibility of agricultural technology.…”
Section: Introductionmentioning
confidence: 96%
“…The annual income of mini-tiller users and bullock user farmers was found to be statistically significant at a 1% level of significance. GC et al (2019) and (Moniruzzaman et al, 2021) also revealed that income is the major determinant for investment in mechanization. Similarly, the average land holding was found to be 0.64 ha and 0.42 ha by the mini-tiller user and bullock users respectively.…”
Section: Socio-demographic Characters Of Continuous Variablesmentioning
confidence: 97%
“…To focus specifically on farm mechanization, the government of Nepal for the first time formulated the Agriculture Mechanization Promotion Policy (AMPP) on 13 August 2014 intending to promote agriculture mechanization and commercialization in agriculture. Facilitation of credit access, capital subsidies on agricultural machinery purchases, promotion of multipurpose machinery, separate number plates for subsidized vehicles used for agriculture, human resource development, and intellectual property rights for indigenous knowledge are the key provisions of the AMPP 2071 (GC et al, 2019). Despite decades of investment and effort in mechanization in Nepal, the results are still inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…In Nepal, just 8 per cent of farmers use tractors, 26 per cent use iron plows (Kaur, 2017). Study carried out by GC et al, (2019) showed that light machinery is an essential part of Nepali farming system. Marahatta et al (2018) found higher yield of both rice and wheat (4106; 3042 kg ha -1 ) in conservation agriculture than conventional agriculture (4106; 3022 kg ha -1 ).…”
mentioning
confidence: 99%